1997
DOI: 10.1097/00005537-199702000-00019
|View full text |Cite
|
Sign up to set email alerts
|

One‐Stage Reconstruction of Partial Laryngopharyngeal Defects

Abstract: Advanced-stage lesions of the hypopharynx or tongue base often involve the larynx. The difficulty of reconstructing large partial laryngopharyngeal defects can result in total laryngectomy being performed to avoid the assumed problems with aspiration. This article describes the first reported experience using the pectoralis musculocutaneous flap for primary one-stage reconstruction of laryngopharyngeal defects following resection of advanced-stage lesions, to reconstruct both the laryngeal and the pharyngeal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Contemporary reconstructive tissue transferring techniques have also improved the chances of preserving function. The literature now includes descriptions of techniques using musculocutaneous flaps 28 or free flaps 29 demonstrating that important organs such as the larynx and pharynx do not have to be totally resected but can be reconstructed in such a fashion to preserve swallowing and speaking function.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary reconstructive tissue transferring techniques have also improved the chances of preserving function. The literature now includes descriptions of techniques using musculocutaneous flaps 28 or free flaps 29 demonstrating that important organs such as the larynx and pharynx do not have to be totally resected but can be reconstructed in such a fashion to preserve swallowing and speaking function.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of local reconstruction techniques and the use of regional pedicled flaps allowed resection of these lesions while maintaining separation of the aerodigestive tract from the neck. Schuller et al 7 reported using the pectoralis major flap to reconstruct partial laryngopharyngeal defects. In this series, only 1 of 21 patients had to be converted to a total laryngectomy owing to aspiration, and 31 of 43 patients (72%) had some oral intake.…”
Section: Commentmentioning
confidence: 99%
“…Surgery, usually in combination with postoperative radiotherapy, is believed to provide the highest cure and local control rates in patients with cancer of the hypopharynx 2–5 . Even more important, surgery provides immediately successful and long‐lasting palliation for airway obstruction, obstructive dysphagia, and aspiration since local control is frequently achieved even in locally advanced cancer 6–10 . However, the risks of surgery (bleeding, fistula, infection, and death) are too high to perform laryngopharyngectomy for patients with unresectable disease and for those presenting with poor performance status.…”
mentioning
confidence: 99%